ANALYSIS OF EXPERIENCES TEXT RELATIONSHIP (ETR) METHOD IN THE JOURNAL ARTICLE - Lesi Erawati; Agus Triyogo; yulfi yulfi (Journal of English Education, Literature and Linguistics, 2022)
Reading was an activity of seeing, observing a series of written symbols and understanding the information contained in a paragraph. Reading be important skill that must be mastery by students. The aimed of the research were to describe the students’ problem in learning Reading Comprehension and to describe Experiment-Text-Relationship (ETR) method play a role in improving students' reading comprehension. This research designed in qualitative method that focused in library research. The subject in this research was seven articles that published in the journals. In collecting the data, the writer reding research article in ETR and in analyzing the data, the writer identifying and classifiying. The results showed : students had less spirit in following the lesson and they confuse about understanding part of the reading skills. After used Experiment-Text-Relationship (ETR) method, students’ score were increase ftom the post test data. It can be concluding that Experiment-Text-Relationship (ETR) method as solution in teaching reading comprehension.